A novel method to enhance methane hydrate exploitation efficiency via forming impermeable overlying CO2 hydrate cap. (15th April 2019) - Sun, Zhen-Feng; Li, Nan; Jia, Shuai; Cui, Jin-Long; Yuan, Qing; Sun, Chang-Yu; Chen, Guang-Jin
Highlights: A new idea " reservoir reformation " is proposed to prevent sea water from invading NGH zone. An artificial impermeable overlying CO2 hydrate cap is constructed successfully. The CO2 hydrate cap improves production efficiency by decreasing water yield. Optimal CO2 /H2 O volume ratio of the emulsion is suggested to form the desired CO2 hydrate cap. Large amounts of CO2 is sequestrated in the depleted CH4 hydrate zone. Abstract: To enhance the exploitation efficiency of natural gas hydrate by decreasing the yield of water, a novel "reservoir reformation" concept is proposed that involves the reformation of a natural gas hydrate reservoir by constructing an artificial impermeable overlying CO2 hydrate cap. The feasibility of this concept has been demonstrated in this laboratory-scale experiment. After reformation by injecting CO2 emulsion into the permeable overburden, a confined environment with an impermeable CO2 hydrate cap is successfully constructed for depressurization operation. The cap can maintain mechanical stability until the end of production process. With the protection provided by the artificial CO2 hydrate cap, the production efficiency was greatly improved to 83.3% and the water yield is remarkably decreased. Moreover, the optimal CO2 /H2 O volume ratio of the emulsion for forming the desired CO2 hydrate cap was confirmed to be 1:1. The formation of CO2 hydrate cap can also protect the geological stability of depleted methane hydrate zones and seal a large amount of CO2, which is of both energetic and environmental significance; however, intensive and extensive research should be conducted in the future.